2011
DOI: 10.1111/j.1365-2036.2011.04932.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intestinal resection on serum levels of anti‐Saccharomyces cerevisiae antibodies (ASCA) in patients with Crohn’s disease

Abstract: SUMMARY BackgroundAntibodies to Saccharomyces cerevisiae (ASCA) are highly prevalent in sera of patients with Crohn's disease and have been proposed to identify subgroups of patients with a disabling disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 31 publications
1
28
1
Order By: Relevance
“…ASCA positivity was shown to precede symptoms of CD in a cohort of Israeli soldiers who had had serum stored at the time of enlistment to the army and later developed CD [31]. Studies have shown no significant changes in ASCA, anti-OmpC, anti-I2 or ANCA more than 6 months following small bowel surgery [26,32] or following induction of remission with infliximab in those with documented mucosal healing [3]. Further longitudinal studies assessing alterations in serological responses and disease progression are needed, however.…”
Section: Discussionmentioning
confidence: 97%
“…ASCA positivity was shown to precede symptoms of CD in a cohort of Israeli soldiers who had had serum stored at the time of enlistment to the army and later developed CD [31]. Studies have shown no significant changes in ASCA, anti-OmpC, anti-I2 or ANCA more than 6 months following small bowel surgery [26,32] or following induction of remission with infliximab in those with documented mucosal healing [3]. Further longitudinal studies assessing alterations in serological responses and disease progression are needed, however.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, serum ASCA levels remain stable after curative intestinal resection in CD [75], indicating the persistence of both the stimulus and immunological mechanisms operative in the production of ASCA even after complete surgical resection of macroscopically inflamed intestinal tissue, or alternatively indicating that longer time is needed for the loss of antibody response as suggested by the data from the celiac literature [76]. Similarly in a study by Rieder et al, it was observed that a variation in titer, but not marker positivity, was reported for antiglycan antibodies in medically or surgically induced remission [77].…”
Section: Serology Markersmentioning
confidence: 99%
“…Eser et al [115] reported stable ASCA levels before and after intestinal resection. No significant changes in serological responses toward ASCA, anti-I2 and Omp-C after small-bowel surgery with or without fecal diversion were found [84,86,121].…”
Section: Antimicrobial Antibody Levels During Disease Coursementioning
confidence: 99%
“…Eser et al [115] examined a possible link between preoperative ASCA levels and the risk of surgical recurrence. After intestinal resection, neither ASCA positivity nor ASCA serum levels predicted the risk of surgical recurrence during long-term follow-up (median of 106 months).…”
Section: In What Clinical Situations Do We Need An Argument For Earlymentioning
confidence: 99%
See 1 more Smart Citation